(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2021)
This article aims to do an aesthetic and technical analysis of the creative process of the making of the short film “windows of the soul” by the director Jonas Estevão, developed at the second academic semester of 2020 at the Federal University of Ouro Preto, under orientation of the Professor Doctor Letícia Andrade, professor of Theatrical Lighting Design of the Arts Departament of the Philosophy and Arts Institute of the same University. The text describes how the Scenic Lighting was the main trigger of the aesthetic and narrative construction of the work.